Pengaruh Model Problem-Based Learning Berbantuan Question Prompt Scaffolding Terhadap Keterampilan Argumentasi Ilmiah Siswa SMP dalam Pembelajaran IPA - Alicia Dewi Nazarina (Faculty of Teaching Training and Education, 2026)
In this increasingly competitive modern era, students are not only required to master theoretical material but must also possess strong communication skills to face global challenges. One manifestation of these skills is scientific argumentation, which has now become a crucial competency included in the learning outcomes for science. The importance of this competency lies in its dual function: it enhances communication skills and helps students develop critical thinking to meet each learning indicator. As a learning outcome, scientific argumentation skills must, of course, be taught to students through the design of appropriate learning scenarios. Problem-based learning is an appropriate model because it emphasizes solving real-world problems as the core of the learning process. However, in practice, the transition toward independent thinking often causes many students to face technical difficulties, necessitating specialized assistance or approaches to bridge these gaps in understanding. Question prompt scaffolding is a technique involving guided questions typically incorporated into the learning process to support teaching and learning activities. This study is a quantitative descriptive study, which explains the phenomena occurring based on numerical data from scientific argumentation test results. This study was conducted to identify the level of students’ scientific argumentation skills influenced by the problem-based learning model supported by question prompts in science education.
Validasi dan Finalisasi Repositori File 15 Juni 2026_Kholif Basri
Keywords: Scientific Argumentation; Problem-Based Learning; Question Prompt